2013
DOI: 10.1099/jmm.0.048678-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of biofilm maturation by linezolid in meticillin-resistant Staphylococcus epidermidis clinical isolates: comparison with other drugs

Abstract: Biofilm resistance mechanisms are multifactorial and vary from one organism to another. The purpose of this study was to investigate the efficacy of linezolid against indwelling device-related meticillin-resistant Staphylococcus epidermidis (MRSE) biofilm, and compare this with other antimicrobials. MICs, minimum biofilm inhibitory concentrations (MBICs) and minimum biofilm eradication concentrations (MBECs) were determined by the microtitre plate method. Fourteen and thirteen isolates from patients with indwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Reiter et al . () studied the activity of rifampicin, individually and in combination with vancomycin, against biofilm producer isolates of MRSA. They found greater inhibition of bacterial growth after combined drug use than after use of each drug individually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reiter et al . () studied the activity of rifampicin, individually and in combination with vancomycin, against biofilm producer isolates of MRSA. They found greater inhibition of bacterial growth after combined drug use than after use of each drug individually.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, another synergism that was observed to present a good activity against MRSA isolates was rifampicin (2 lg ml À1 ) plus vancomycin (4 lg ml À1 ). Reiter et al (2012) studied the activity of rifampicin, individually and in combination with vancomycin, against biofilm producer isolates of MRSA. They found greater inhibition of bacterial growth after combined drug use than after use of each drug individually.…”
Section: Figurementioning
confidence: 99%
“…Such susceptibility differences between the culture states of the bacteria can have various causes, including the difference in diffusion of the antimicrobial agent Ceri et al, 1999, Wilson, 1996, Costerton et al, 1995 Recently, the minimum biofilm inhibitory concentration MBIC and minimum biofilm eradication concentration MBEC have been proposed as experimental benchmarks for evaluating antimicrobial activity against biofilms Reiter et al, 2013, Anwar et al, 1990,Sandoe et al, 2002 . The MBIC of the antimicrobial agent is the minimum concentration at which the growth of the biofilm bacteria is inhibited, and the MBEC is the minimum concentration at which 99.9% of the biofilm bacteria are eradicated Ceri et al, 1999, Reiter et al, 2013 Streptococci are bacteria that initially attach to tooth surfaces Kara et al, 2006, Kolenbrander et al, 2002 They are present in a large number in plaques, and have a wide range of properties that allow them to adhere to pellicle components as well as other bacterial species through a coaggregation mechanism Blanc et al, 2014 . Many previous studies have observed the antibacterial effects of chlorhexidine and cetylpyridinium chloride, alone and in mouthwash formulations, on oral bacteria Koljalg et al, 2002, Gehlen et al, 2000, Kitagawa et al, 2016, Andre et al, 2011 determine the MIC and MBC.…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…Antimicrobial susceptibility testing of the bacterial biofilms was performed using a previously reported method Ceri et al, 1999, Reiter et al, 2013, Cafiso et al, 2010 In brief, to form biofilm on the bottom of a 96-well plate SPL flat-bottom plates , 180 µL of BHI medium and 20 µL of bacterial suspension adjusted to 0.5 McFarland standard 1 10 8 CFU/mL were added to the plates and cultured in a 5% CO 2 incubator at 37 for 18 h. After incubation, each microplate was washed three times with BHI medium to remove any non-adherent bacterial cells. Each antimicrobial agent was diluted serially in BHI medium in a new microplate, and the diluted solution was transferred to the microplate with biofilm, which was then cultured at 37 for 18 h. After incubation, the turbidity of the supernatant was observed and the minimum concentration at which bacterial growth was inhibited was determined as the MBIC.…”
Section: Determination Of the Mbic And Mbecmentioning
confidence: 99%
See 1 more Smart Citation